2019
DOI: 10.1177/0018720819854880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Semantic Congruence on Sign Identification: An ERP Study

Abstract: Objective The purpose of this study was to investigate the effects of semantic congruence and incongruence on sign identification by using event-related potentials (ERPs). Background Sign systems have crucial roles in public spaces and traffic facilities. Poorly designed signs can easily confuse pedestrians and drivers and reduce the efficiency of public activities and urban administration. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
5
23
0
Order By: Relevance
“…They suggested that N400 reflects a crucial unconscious categorization in the selection of branded products. N400 has been reported to be mainly distributed in the frontal regions in studies using word–word combinations ( Hamm et al, 2002 ; Schneider et al, 2014 ) and in the parietal and occipital regions in studies using picture–word combinations ( Ma et al, 2016 ; Lu and Hou, 2020 ). In the current study, N400 was distributed in the occipital regions, which is consistent with the results of previous studies ( Ma et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They suggested that N400 reflects a crucial unconscious categorization in the selection of branded products. N400 has been reported to be mainly distributed in the frontal regions in studies using word–word combinations ( Hamm et al, 2002 ; Schneider et al, 2014 ) and in the parietal and occipital regions in studies using picture–word combinations ( Ma et al, 2016 ; Lu and Hou, 2020 ). In the current study, N400 was distributed in the occipital regions, which is consistent with the results of previous studies ( Ma et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that presenting people with verbal stimuli that they perceive as exhibiting semantic conflict can elicit N400 ( Barrett and Rugg, 1990 ). N400 has been found to be effective for detecting semantic conflict in non-verbal stimuli ( Ma et al, 2016 ; Lu and Hou, 2020 ). The current study found that N300 and N400 can be used to detect the expected consistency between products and their prices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has shown that ERPs are conducive to understanding how people process safety signs (Fu et al, 2017;Ma et al, 2018;Lu and Hou, 2019;Bian et al, 2020;Zhu et al, 2020). For instance, warning signs with higher hazard levels are associated with increased N1, N2, and P300/LPP components (Ma et al, 2010(Ma et al, , 2018Fu et al, 2017;Bian et al, 2020), and a reduced P2 component (Ma et al, 2018;Bian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%